Chemotherapeutic efficiency of drugs in vitro: Comparison of doxorubicin exposure in 3D and 2D culture matrices. (June 2016) - Casey, A.; Gargotti, M.; Bonnier, F.; Byrne, H.J.
Abstract: The interest in the use of 3D matrices for in vitro analysis, with a view to increasing the relevance of in vitro studies and reducing the dependence on in vivo studies, has been growing in recent years. Cells grown in a 3D in vitro matrix environment have been reported to exhibit significantly different properties to those in a conventional 2D culture environment. However, comparison of 2D and 3D cell culture models have recently been noted to result in differing responses of cytotoxic assays, without any associated change in viability. The effect was attributed to differing conversion rates and effective concentrations of the resazurin assay in 2D and 3D environments, rather than differences in cellular metabolism. In this study, the efficacy of a chemotherapeutic agent, doxorubicin, is monitored and compared in conventional 2D and 3D collagen gel exposures of immortalized human cervical cells. Viability was monitored with the aid of the Alamar Blue assay and drug internalisation was verified using confocal microscopy. Drug uptake and retention within the collagen matrix was monitored by absorption spectroscopy. The viability studies showed apparent differences between the 2D and 3D culture systems, the differences attributed in part to the physical transition from 2D to a 3D environment causing alterations to dye resazurin uptake and conversion rates. The use of 3D culture matrices has widely been interpreted to result in "reduced" toxicity or cellular "resistance" to the chemotherapeutic agent. The results of this study show that the reduced efficiency of the drug to cells grown in the 3D environment can be accounted for by a sequential reduction of the effective concentration of the test compound and assay. This is due to absorption within the collagen gel inducing a higher uptake of both drug and assay thereby influencing the toxic impact of the drug and conversion rate of resazurin, and. The increased effective surface area of the cell exposed to the drug and assay in the 3D environment. The effect was noted to be higher after shorter exposure periods and should be accounted for in in vitro 2D and 3D culture environment comparisons. Highlights: Cellular viability is different between the 2D and 3D culture systems. False reduced efficiency of the drug to cells grown in the 3D environment 3D exposure results in absorption within gel of both compound and test assay.